Benefits of breast milk for health care: analysis from the Islamic perspective - Daud, Normadiah; Ismail, Hamizah; Mohd Arifin, Siti Roshaidai; Embong, Rahimah; Nordin, Nadhirah; Abdu Bichi, Ado (Indianjournals, 2019)
Breastfeeding truly gives an enormous effect towards the health of a mother and child. Breast milk contains nutrients which are highly beneficial for an infant’s health and growth. Among other benefits for a baby is it helps to develop the baby’s intelligence, it is very clean and it can save a baby from various diseases. There are lots of explanations in Islam with regards to the important position of breast milk in the life of a child however; there is lack of empirical evidences pointing out the importance of breastfeeding for health care from the Islamic perspective. In view of these the present paper aimed at studying the importance of breastfeeding for both child and mother according to the perspectives of Islam. This research is based on literature review method. Data was collected through documents analysis which consists of turath (traditional) and modern books as well as articles related to breastfeeding. The review revealed the importance of breast milk for a baby’s health; apparently the opinions of scientists are in parallel with the opinions of fuqaha. In fact, fuqaha from Shafi’i and Hambali sects obliged the feeding of al laba’ which is colostrum to newborn babies. Conclusively, Muslims are made by the Islamic injunctions to believe that breast milk is just an effort to prevent a child and a mother from being inflicted with any diseases. This paper provides an important highlight that the breastfeeding is not only significance according to science but also because it fulfils the syarak requirements.